วรรณกรรมเพลงเปียโนสำคัญสำหรับเดี่ยวมือซ้าย - ปานใจ จุฬาพันธุ์ (วิทยาลัยดนตรี มหาวิทยาลัยรังสิต, 2021)
This article explores piano literatures for the left hand alone. Those works contain advanced techniques since both melodies and accompaniments have to be presented by the left hand only. Furthermore, artistic flexibility and relaxed gestures are also required in order to zoom over the higher and lower ranges of the entire keyboard. Skillful pedal usage is also recommended in order to connect all the voices. Repertoires for the left hand alone including exercises, etudes, and advanced compositions for piano solo and piano with an orchestra are those composed by piano teachers and noted composers like Czerny, Hofmann, Leschetizky, Wittgenstein, and Ravel. The survey of piano works for the left hand alone will extend Thai pianists’ view of compositions in this genre and therefore enable to guide them to choose appropriate pieces for technique development and performances in various occasions.